A Review on Application of Global Positioning System in Construction Industry - Nair, Pravinath; Abd Sukor Sarif (Progress in Engineering Application and Technology, 2022)
Construction activity is fraught with many uncertainties such as managing workers, machines, and safeties. Various of strategies have been devised to prevent construction productivity and quality deterioration due to difficulties in managing construction works. This paper discusses the application of GPS technology in the construction industry. Followed by what type of GPS positioning method is used and how well the implementation of GPS technology improves the efficiency and productivity in the construction field. Nowadays, many components of technologies, such as augmented reality, wireless communication, and client–server databases, were used to efficiently control, transfer, and view project data on a mobile with the help of Global Positioning system (GPS) in construction project. In this case, a lot of published studies were looked at, and it was found that GPS can be used to keep track of construction progress, order materials, track construction vehicles, equipment, and workers, and more. So, this paper identifies some possible research where GPS was being implemented in construction industries to improve the efficiency and productivity.